2016
DOI: 10.1242/dev.126797
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase III component Rpc9 regulates hematopoietic stem and progenitor cell maintenance in zebrafish

Abstract: Hematopoietic stem and progenitor cells (HSPCs) are capable of self-renewal and replenishing all lineages of blood cells throughout the lifetime and thus critical for tissue homeostasis. However, the mechanism regulating HSPC development is still incompletely understood. Here, we isolate a zebrafish mutant with defective T lymphopoiesis and positional cloning identifies that Rpc9, a component of DNA-directed RNA polymerase III (Pol III) complex, is responsible for the mutant phenotype. Further analysis shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…1D). Moreover, the expression of rac2 was absent in a T cell-deficient mutant line-rpc9 mutant, which is reported in our previous study (38) (Supplemental Fig. 1A), suggesting its role in T lymphoid progenitors.…”
Section: Rac2 Is Expressed In T Lymphoid Progenitors During Zebrafish Embryogenesissupporting
confidence: 82%
See 1 more Smart Citation
“…1D). Moreover, the expression of rac2 was absent in a T cell-deficient mutant line-rpc9 mutant, which is reported in our previous study (38) (Supplemental Fig. 1A), suggesting its role in T lymphoid progenitors.…”
Section: Rac2 Is Expressed In T Lymphoid Progenitors During Zebrafish Embryogenesissupporting
confidence: 82%
“…Proteins were purified in radioimmunoprecipitation assay buffer. Western blotting analyses were conducted as described previously (38). Ab used for Western blotting included anti-b-actin (1:2000; Cell Signaling Technology), anti-Rac2 (1:200; Santa Cruz Biotechnology), anti-AKT (1:1000; Cell Signaling Technology), anti-pAKT (1:500; Cell Signaling Technology), anti-Pak1 (1:200; Cell Signaling Technology), and anti-pPak1 (1:500; Cell Signaling Technology).…”
Section: Immunofluorescence and Western Blottingmentioning
confidence: 99%
“…The cell experiments described above showed that the PKA/TFAM pathway could enhance COXIV expression to reduce ROS levels. To verify the molecular pathway in vivo , day 2 DP were injected with the PKA agonist forskolin (FSK) to elevate p‐PKA levels [34], and the results showed that both TFAM and COXIV levels in brains were increased significantly (Figs 5A and S4A). In contrast, day 2 NP were injected with the PKA inhibitor H89, and the results showed that TFAM and COXIV levels decreased as did the p‐PKA level (Figs 5B and S4B).…”
Section: Resultsmentioning
confidence: 99%
“…Expression of a splice mutant of the POLR3B subunit in zebrafish led to a disruption in the digestive organ and size reductions in other organs ( Yee et al, 2007 ). Furthermore, deficiency of rpc9 , another RNA pol III subunit, impaired hematopoietic stem and progenitor cell development in zebrafish ( Wei et al, 2016 ). How specific changes in RNA pol III-dependent transcription affect these processes remains undetermined.…”
Section: Discussionmentioning
confidence: 99%